2022
DOI: 10.19083/ridu.2022.1569
|View full text |Cite
|
Sign up to set email alerts
|

Análisis descriptivo y tendencias de las tesis de pregrado en Facultades de Odontología peruanas

Abstract: Introducción: El análisis de tesis de odontología en el Perú proporciona información valiosa para optimizar esfuerzos relacionados a solucionar problemas de salud bucal. Objetivo: analizar tesis de pregrado de odontología, de universidades peruanas durante 2015–2019. Método: estudio descriptivo, asociativo y cuantitativo. Se analizaron 1,389 tesis de 14 universidades públicas y privadas. Las variables: nombre de la universidad, tipo de universidad, número de autores, acceso a texto completo o resumen, área aca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
2
2
0
Order By: Relevance
“…In this study, most of the theses were defended in private universities (65.9%), which is similar to that reported by Moromi-Nakata et al (2022) in Peru. This result is related to the higher number of private universities with dentistry faculties and, therefore, of enrollment and graduates who defend thesis.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In this study, most of the theses were defended in private universities (65.9%), which is similar to that reported by Moromi-Nakata et al (2022) in Peru. This result is related to the higher number of private universities with dentistry faculties and, therefore, of enrollment and graduates who defend thesis.…”
Section: Discussionsupporting
confidence: 88%
“…When analyzing the methodological designs of the thesis, it was found that most of them were observational, descriptive, and cross-sectional, which is similar to what has been reported in previous research on theses in undergraduate health sciences in Colombia (Cruz Mosquera et al, 2021) and Peru (Taype-Rondán et al, 2012;Mejia et al, 2014;Castro-Rodríguez et al, 2018a,b;Quispe et al, 2019;Castro-Rodríguez et al, 2020;Moromi-Nakata et al, 2022;Angulo-Fernandez et al, 2023;Castro-Rodríguez et al, 2023a,b) but contrasts with what has been reported in another Peruvian study (Aragón-Ayala et al, 2023). This result may be due to the fact that these designs, in methodological terms, are less complex and do not require large investments or follow-ups as in other designs, making them more attractive and feasible for students and tutors (Gutiérrez and Mayta, 2003).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations